Social and cognitive perspectives on the Sermon on the Mount - Roitto, Rikard 1974-; Shantz, Colleen; Luomanen, Petri 1961- (Sheffield, UK Bristol, CT Equinox Publishing Ltd, 2021)
Perception of risk in the Sermon on the Mount / Rikard Roitto -- Parables in the Sermon on the Mount-a cognitive and rhetorical perspective / Lauri Thuré -- Macarisms and identity formation : insights from the comparison of 4QBeatitudes and the Sermon on the Mount / Elisa Uusimäki.
"Social and Cognitive Perspectives on the Sermon on the Mount offers fresh readings of themes and individual sayings in the Sermon on the Mount using socio-cognitive approaches"--
Literaturangaben
Keywords: Sermon on the Mount -- Criticism, interpretation, etc; Sermon on the Mount -- Socio-rhetorical criticism; Psychology, Religious